URGENSI SPIRITUAL MARKETING SEBAGAI MEDIA PEMASARAN PARIWISATA DI MADURA (PENDEKATAN SHARIA TOURISM AND CULTURE) - Fahrudin, Muhammad Arif; Kholidiyanti, Nina Amiliya; Mois, Fathul Arifin (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2017)
So far, business and marketing practices have only caught on to rational and emotional considerations. The spiritual aspect tends to be ignored, as evidenced by the outbreak of financial scandals in the United States with the collapse of giant corporations, such as Enron, WorldCom, or Global Crossing. So the necessary paradigm shift thinking in the concept of marketing.Spiritual marketing comes to be the solution to the problem. The concept of spiritual marketing developed by Hermawan Kertajaya, we use as a medium of tourism marketing in Madura with sharia tourism and culture approach in accordance with the characteristics of Madurese society that is religious and full of cultural nuances. In the concept of Spiritual Marketing there are four variables: theistic (rabbaniyah), ethical (akhlaqiyyah), realistic (a-waqi'iyyah), and humanist (insaniyyah) that will guide in this concept. Spiritual marketing has an orientation to God, so the whole process in marketing activities follows the guidance of Islam.The method used in this paper is qualitative descriptive with primary and secondary data. This concept requires synergy between government, religious leaders, academics, MUI, and society in Madura so that its implementation can take place and produce positive results for the progress of tourism in Madura.